2008
DOI: 10.1016/j.jpedsurg.2008.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Donor major histocompatibility complex class I expression determines the outcome of prenatal transplantation

Abstract: Background/Purpose-The failure of in utero transplantation in immune-competent recipients suggests the existence of a fetal immune barrier. The importance of donor MHC class I expression in the induction of prenatal tolerance remains undefined. We hypothesized that donor cell MHC class I expression facilitates engraftment in prenatal allogeneic recipients rather than promoting immune rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The studies by Kim et al (1998 , 1999 ) first demonstrated that allospecific T cell tolerance can be reliably achieved by IUHCT to the murine fetus at E14 resulting in the deletion and anergy of donor-reactive T cells. Subsequent studies confirmed the allo-receptivity of C57BL/6 and Balb/c fetuses at E14 ( Shaaban et al, 1999 , 2006 ; Hayashi et al, 2002 ; Durkin et al, 2008a , b ; Alhajjat et al, 2013 ; Nijagal et al, 2013 ). Collectively, these findings suggest that the potential for donor-specific tolerance to reliably develop following IUHCT is lost shortly after the appearance of mature single positive T cells.…”
Section: Fetal T Cells Are Unlikely To Act Alone In Rejection After Imentioning
confidence: 70%
See 2 more Smart Citations
“…The studies by Kim et al (1998 , 1999 ) first demonstrated that allospecific T cell tolerance can be reliably achieved by IUHCT to the murine fetus at E14 resulting in the deletion and anergy of donor-reactive T cells. Subsequent studies confirmed the allo-receptivity of C57BL/6 and Balb/c fetuses at E14 ( Shaaban et al, 1999 , 2006 ; Hayashi et al, 2002 ; Durkin et al, 2008a , b ; Alhajjat et al, 2013 ; Nijagal et al, 2013 ). Collectively, these findings suggest that the potential for donor-specific tolerance to reliably develop following IUHCT is lost shortly after the appearance of mature single positive T cells.…”
Section: Fetal T Cells Are Unlikely To Act Alone In Rejection After Imentioning
confidence: 70%
“…Improved competition for available host niches would logically lead to higher levels of early chimerism. Previous reports from our group illustrate that the early chimerism level (discussed below) is the major determinant of successful allogeneic engraftment and link this to the development of donor-specific NK cell tolerance ( Shaaban et al, 2006 ; Durkin et al, 2008a , b ; Alhajjat et al, 2013 ). However, a competitive-niche model struggles to explain the dichotomous observations for immunodeficient vs. non-immunodeficient cases and seems to disregard the obvious difference.…”
Section: The Clinical Paradigm For Prenatal Transplantationmentioning
confidence: 88%
See 1 more Smart Citation
“…In this instance, the frequency of engraftment of B6 FL in Rag1 -/-recipients was 89% (Figure 2A, n = 9, c 2 test, P = 0.83 compared with congenic controls), indicating that the barrier to IUHCTx in our model was likely due to an adaptive alloimmune response. While NK cells have been shown to be important in engraftment after IUHCTx (22,23), their effect can be overcome using high-cell doses, as we are doing in this model (24). As expected, the overall levels of chimerism in these animals were much higher (59.2% ± 7.2% compared with 22.2% ± 4.5% for allogeneic wild-type recipients, P = 0.0001), likely secondary to the competitive advantage of transplanted cells in the Rag1 -/-hosts (ref.…”
Section: Figurementioning
confidence: 99%